Isolated sphenoid sinus lesion: A diagnostic dilemma - Alazzawi, Sarmad (Bloomsbury Qatar Foundation Journals, 2014)
Isolated sphenoid sinus lesions are an uncommon entity and present with non-specific symptoms. In this case report, the patient presented with a history of headaches for a duration of one month without sinonasal symptoms. A computed tomography scan showed a soft tissue mass occupying the sphenoid sinus. An endoscopic biopsy revealed fungal infection. Endoscopic wide sphenoidotomy with excision of the sphenoid sinus lesion was then performed however, the microbiological examination post-surgery did not show any fungal elements. Instead, Citrobacter species was implicated to be the cause of infection.